Is there a role of antisperm antibodies in women with unexplained infertility - a Turkish pilot cross sectional case control study (Annals of Medical Research, 2021)
Aim: Although some studies indicate that the presence of antisperm antibody (ASA) is important in the etiology of female infertility, this remains a controversial issue. The aim of this study was to determine whether the presence of ASA was important or not in primary and secondary unexplained infertility patients.Materials and Methods: Female patients (n = 90) were divided into three groups as follows: the primary infertility group (n = 30), the secondary infertility group (n = 28) and a control group (n = 32). In addition to laparoscopic evaluations, the presence of ASA in the study groups was also examined in serum and peritoneal washing liquid. The ASA - immunoglobulin G was measured using the Enzyme-Linked ImmunoSorbent Assay (ELISA) method with a qualitative measurement kit.Results: When the demographic data were analyzed, it was observed that the study groups were homogeneous in terms of age and period of infertility. The results of the study demonstrated that, when compared to the secondary infertility and control groups, the ASA positivity in the serum in the primary infertility group was significant (p < 0.05). However, when the groups were compared, there was no difference in terms of ASA positivity in peritoneal washing fluid (p > 0.05).Conclusion: This study showed that the presence of ASA in serum may be an impact on the etiology of unexplained primary infertility.
Keywords: Antisperm antibody; immunoglobulin G; primary infertility; secondary infertility; unexplained infertility